Nilai Strategis Isu Lingkungan dalam Politik Indonesia - Cornelis Lay (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2007)
Environmental issues have been central in the current global potitics and discourse. Furthermore, environment has been set as one of the most important global constitution. Environmental issues have created a complex political network across the world. In Indonesia, howaver, environmental issues have not been seen as central in policy making processes. This paper shows how in most of policy making processes environmental issues end up merely with documents and rhetoric rather than political actions. This paper also argues that 'politics' should be used to deal with paradox in managing environment: gaining benefit and minimizing risk.